Method for preparing fluorine-containing mine water treatment agent from all-component coal gangue and application of fluorine-containing mine water treatment agent
Through ball milling and high-temperature roasting, the polymer aluminum chloride coagulant and fluorine-depleted adsorbent are prepared, which solves the problems of coal gangue solid waste treatment and fluorine-containing mine water treatment, and achieves efficient treatment and comprehensive resource utilization.
Patent Information
- Application Number
- CN202510444226.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-10
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-04-10
AI Technical Summary
In the prior art, coal gangue produces a large amount of silicon-based solid waste when preparing aluminum salt coagulants, resulting in waste of resources and environmental pollution, and it is difficult to efficiently treat fluorine-containing mine water.
Through ball milling and high-temperature roasting, polymer aluminum chloride coagulant and fluorine-depleted adsorbent are prepared, combined with acid leaching and rare earth modification treatment, to achieve efficient treatment of fluorine-containing mine water and on-site treatment and comprehensive utilization of coal gangue solid waste.
It has achieved efficient treatment of fluorine-containing mine water, removed suspended matter and fluorine ions, and effectively utilized coal gangue solid waste, avoiding resource waste and environmental pollution.
Smart Images

Figure CN119954282A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of resource utilization of coal gangue, and specifically relates to a method for preparing a fluorine-containing mine water treatment agent by utilizing coal gangue in all components and application thereof. Background Art
[0002] The problem of excessive fluoride has become one of the main challenges for the efficient use of mine water in my country's mining areas. After the mine water is treated to meet the standards, the comprehensive utilization methods mainly include underground production and living water in coal mines, ecological irrigation in mining areas, and water for residents in mining areas. The corresponding standards are "Drinking Water Hygiene Standard (GB5749-2022)" (where the fluoride concentration limit is 1 mg / L) and "Surface Water Environmental Quality Standard (GB3838-2002)" (the fluoride concentration limit for surface water Class I, II, and III is 1 mg / L). At present, the main treatment methods for fluoride-containing mine water include chemical precipitation, adsorption, ion exchange, membrane separation, etc. Among them, the adsorption method is widely used due to its simple operation, high efficiency and low cost.
[0003] Gangue is a kind of rock that coexists with coal seams and is a solid waste generated during coal mining and washing. Its main component is aluminosilicate, which contains about 40-60% SiO2 and 15-50% Al2O3, and is an excellent silicon-aluminum mineral raw material. However, due to its low activity, the utilization efficiency of gangue is not high, resulting in a large amount of gangue being piled up in mining areas, causing serious waste of resources, environmental pollution and economic losses. Therefore, processing gangue to produce high value-added products will have certain economic and environmental benefits.
[0004] The use of coal gangue acid method to prepare aluminum salt coagulant for water treatment has the advantages of fast floc formation, good precipitation performance, low alkalinity consumption in water, and strong adaptability to changes in water temperature, pH value, turbidity and organic matter content. In the prior art, when using coal gangue to prepare aluminum salt coagulant, a large amount of silicon-based solid waste will be generated. If these silicon-based solid wastes are not effectively treated, they will not only cause waste of resources, but also cause secondary pollution to the environment. Summary of the invention
[0005] In order to overcome the above technical problems, the purpose of the present invention is to provide a method and application of preparing a fluorine-containing mine water treatment agent using coal gangue as all components. The method prepares polyaluminium chloride coagulant by acid leaching, and uses rare earth modified acid leaching residue to prepare a defluorination adsorbent, which is applied to the treatment of fluorine-containing mine water, achieving efficient treatment of fluorine-containing mine water, and at the same time achieving on-site treatment and comprehensive utilization of coal gangue solid waste.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is: A method for preparing a fluorine-containing mine water treatment agent using coal gangue as all components, comprising the following steps; Step (1): grinding the coal gangue block by a ball mill and then sieving it into coal gangue powder; Step (2): placing the gangue powder obtained in step (1) in a muffle furnace for high-temperature calcination and activation, and then naturally cooling the furnace to obtain activated gangue; Step (3): dispersing the activated coal gangue obtained in step (2) in a hydrochloric acid solution, centrifuging the solid-liquid mixture after the acid leaching reaction, and obtaining a supernatant as an aluminum chloride solution and a precipitate as coal gangue acid leaching residue; Step (4): adding sodium aluminate to the aluminum chloride solution obtained in step (3), adjusting the pH value of the reaction system to 3 to 5, performing a polymerization reaction and aging to obtain a polyaluminum chloride coagulant; Step (5): washing the coal gangue acid leaching residue obtained in step (3) with deionized water for three times and then drying it, adding lanthanum nitrate and cerium sulfate solution, stirring at 25-45° C. for 1-1.5 h to fully impregnate it to obtain coal gangue acid leaching residue loaded with cerium and lanthanum; Step (6): after drying, the cerium and lanthanum loaded on the coal gangue acid leaching slag obtained in step (5) is placed in a muffle furnace for high-temperature roasting to obtain a defluorination adsorbent; Step (7): the polyaluminium chloride coagulant removes suspended matter in the fluorine-containing mine water, and the defluorination adsorbent removes fluoride ions in the fluorine-containing mine water. The polyaluminium chloride coagulant and the defluorination adsorbent together constitute a fluorine-containing mine water treatment agent.
[0007] Furthermore, the particle size of the coal gangue powder after ball milling in step (1) is 150 mesh.
[0008] The particle size of coal gangue powder is controlled to increase the reaction surface area, thereby improving the efficiency of subsequent reactions, especially the solubility in the acid leaching process.
[0009] Furthermore, in step (2), the high temperature calcination activation is performed at a temperature of 700-850° C. and a calcination time of 1.5-2.5 h.
[0010] The purpose of high temperature roasting is to activate the gangue and improve its chemical reactivity. The temperature range is to adapt to the composition differences of different gangues and avoid excessive roasting that leads to reduced activity.
[0011] Furthermore, the solid-liquid ratio of the activated coal gangue to the hydrochloric acid solution in step (3) is 1:3-1:5; the mass fraction of the hydrochloric acid solution is 20%, the acid leaching temperature is 80-95°C, and the acid leaching time is 1.5-2.5h.
[0012] The purpose of controlling the solid-liquid ratio is to ensure that the acid and gangue can fully contact and react during the acid leaching process, thereby improving the leaching efficiency. Appropriate temperature and time can optimize the rate and efficiency of the acid leaching reaction. At higher temperatures, the reaction rate is faster, but too high a temperature may cause unnecessary side reactions, so it needs to be controlled within a reasonable range.
[0013] Furthermore, in step (4), the polymerization temperature is 70-90°C, the polymerization time is 1-2h, the aging temperature is 20-30°C, and the aging time is 20-30h.
[0014] The temperature and time of the polymerization reaction are set to ensure the full formation of polyaluminium chloride and avoid adverse effects on the polymerization process due to excessively high or low temperatures. The aging reaction helps to improve the stability and performance of the product. By controlling the temperature and time, the reaction is ensured to be completed and the desired product is obtained.
[0015] Furthermore, in step (5), the solid-liquid ratio of the coal gangue acid leaching residue to the lanthanum nitrate and cerium sulfate solution is 1:1-1:3; the molar ratio of lanthanum nitrate and cerium sulfate is 1:1; and the loading ratio of lanthanum and cerium is 15-35%.
[0016] The solid-liquid ratio and molar ratio are set to ensure that the acid leaching residue of coal gangue can fully react with lanthanum nitrate and cerium sulfate solution. The molar ratio of 1:1 can optimize the reaction ratio of rare earth elements to avoid the excess of one element affecting the performance of the product. The range of loading ratio helps to enhance the adsorption effect.
[0017] Furthermore, in step (6), the calcination temperature is 500-650° C., and the calcination time is 0.3-1 h.
[0018] The structural and chemical stability of the material is enhanced by high-temperature calcination. Controlling the temperature and time range helps to fully fix lanthanum and cerium on the surface of the material and optimize the pore structure of the material.
[0019] Another object of the present invention is to provide the use of the fluorine-containing mine water treatment agent composed of a polyaluminium chloride coagulant and a defluorination adsorbent prepared by the above method in the treatment of fluorine-containing mine water.
[0020] The preparation method can prepare polyaluminium chloride coagulant and defluorination adsorbent, wherein the polyaluminium chloride coagulant is used in the coagulation and sedimentation treatment process of mine water, and the defluorination adsorbent is used in the defluorination treatment process. The two are in a front-to-back relationship in the fluorine-containing mine water treatment process, and together achieve efficient treatment of fluorine-containing mine water.
[0021] Beneficial effects of the present invention: (1) The gangue is ball-milled and then sieved into gangue powder. The gangue is crushed into fine powder by ball milling, which significantly increases the contact area of the gangue, making it easier to contact with heat, acid and other media in subsequent roasting activation and acid leaching reactions, thereby improving the reaction efficiency.
[0022] (2) The gangue powder is placed in a muffle furnace for high-temperature calcination and activation, and activated gangue is obtained after the furnace is cooled naturally. High-temperature calcination causes the inorganic components (such as aluminosilicate) in the gangue to undergo thermal decomposition and phase change, forming a porous structure, which increases the chemical activity of the gangue. At the same time, high-temperature calcination can remove organic impurities in the gangue and reduce their interference with subsequent reactions.
[0023] (3) The activated coal gangue is dispersed in a hydrochloric acid solution with a mass fraction of 20%. After the acid leaching reaction, the solid-liquid mixture is centrifuged to obtain an aluminum chloride solution and a precipitate is the coal gangue acid leaching residue. The hydrochloric acid reacts with the aluminum oxide in the activated coal gangue to generate an aluminum chloride solution, which provides raw materials for the subsequent preparation of polyaluminum chloride. The soluble aluminum chloride is separated from the insoluble coal gangue acid leaching residue by centrifugation, thereby realizing efficient utilization of resources.
[0024] (4) Sodium aluminate is added to the aluminum chloride solution until the pH value of the reaction system reaches 3-5, and a polymerization reaction is carried out and matured to obtain a polyaluminum chloride coagulant. The pH value is controlled within the range of 3-5 to ensure that the polyaluminum chloride has a high charge neutralization ability and adsorption bridging effect, which is suitable for the treatment of complex water bodies such as mine water.
[0025] (5) The gangue acid leaching residue was washed three times with deionized water and then dried. Lanthanum nitrate and cerium sulfate solutions were added and stirred at 25°C for 1.5 hours to fully impregnate the residue to obtain gangue acid leaching residue loaded with cerium and lanthanum. The gangue acid leaching residue was washed with deionized water to remove residual hydrochloric acid to avoid interference with the subsequent loading process. Lanthanum nitrate and cerium sulfate were loaded onto the gangue acid leaching residue by impregnation, and the efficient adsorption properties of rare earth elements (cerium and lanthanum) were used to improve the fluoride removal capacity of the material. The introduction of cerium and lanthanum formed more active sites on the surface of the gangue acid leaching residue, significantly improving its adsorption capacity and selectivity for fluoride ions.
[0026] (6) After drying, the gangue acid leaching residue loaded with cerium and lanthanum is placed in a muffle furnace for high-temperature roasting to obtain a defluorination adsorbent. High-temperature roasting allows the rare earth elements to form a stable chemical bond with the surface of the gangue acid leaching residue, preventing the rare earth elements from falling off during use, while further optimizing the pore structure and surface properties of the material. Figure 2 As shown, the surface of the defluorination adsorbent presents a layered structure and has layered crystals. A rich pore structure is formed between these layered crystals, which makes the surface of the defluorination adsorbent have more available adsorption sites, improves its specific surface area and adsorption performance, and is conducive to removing fluoride ions from aqueous solutions.
[0027] The present invention realizes the efficient treatment of fluorine-containing mine water, and simultaneously realizes the on-site treatment and comprehensive utilization of coal gangue solid waste, and has the advantages of being economical, efficient and having a high resource utilization rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a process for preparing coagulants and adsorbents using coal gangue.
[0029] Figure 2 This is a scanning electron microscope photo of the defluorination adsorbent.
[0030] Figure 3 is the amount of fluoride ions adsorbed by the adsorbent in Application Example 3. DETAILED DESCRIPTION
[0031] The present invention will be further described in detail below in conjunction with the accompanying drawings.
[0032] The coal gangue in the examples was purchased from Wuhai Energy Co., Ltd. of the State Energy Group, and lanthanum nitrate and cerium sulfate were purchased from Maclean Company.
[0033] Coal gangue is rich in silicon, aluminum, iron and other elements and is a solid waste; Lanthanum nitrate and fluoride ions have strong electrostatic attraction and can form a stable La-F bond; Cerium sulfate can enhance the adsorption capacity of fluoride ions through valence changes; Preparation Example 1 like Figure 1 As shown, a method for preparing a fluorine-containing mine water treatment agent using coal gangue as all components comprises the following steps; (1) Grinding the lump coal gangue with a ball mill and then sieving to obtain 150 mesh coal gangue powder; (2) placing the gangue powder obtained in step (1) in a muffle furnace and calcining it at 750° C. for 2 h, and then cooling the furnace naturally to obtain activated gangue powder; (3) dispersing the activated gangue powder obtained in step (2) in a 20% by mass hydrochloric acid solution, and centrifuging the solid-liquid mixture after acid leaching at 90° C. for 2.5 h, wherein the supernatant obtained is an aluminum chloride solution, and the remaining solid matter is the gangue acid leaching residue; wherein the solid-liquid ratio of the activated gangue powder to the hydrochloric acid is 1:5; (4) adding sodium aluminate to the aluminum chloride solution obtained in step (3), adjusting the pH value of the reaction system to 3, and then stirring at 80° C. for 1.5 h to carry out polymerization reaction. After the polymerization reaction is completed, aging at 20° C. for 24 h to obtain a polyaluminum chloride coagulant; (5) washing the gangue acid leaching residue obtained in step (3) with deionized water three times and then drying it, adding lanthanum nitrate and cerium sulfate solution, stirring at 25° C. for 1.5 h to fully impregnate it to obtain the gangue acid leaching residue loaded with cerium and lanthanum, wherein the molar ratio of lanthanum nitrate and cerium sulfate is 1:1, and the loading ratio of lanthanum and cerium is 15%; (6) After drying, the coal gangue acid leaching slag loaded with cerium and lanthanum obtained in step (5) is placed in a muffle furnace and calcined at 500° C. for 0.5 h to obtain a defluorination adsorbent.
[0034] Preparation Example 2 (1) Grinding the lump coal gangue with a ball mill and then sieving to obtain 150 mesh coal gangue powder; (2) placing the gangue powder obtained in step (1) in a muffle furnace and calcining it at 800° C. for 2.5 h, and then allowing the furnace to cool naturally to obtain activated gangue powder; (3) dispersing the activated gangue powder obtained in step (2) in a 20% by mass hydrochloric acid solution, and centrifuging the solid-liquid mixture after acid leaching at 85° C. for 2.5 h, wherein the supernatant obtained is an aluminum chloride solution, and the remaining solid matter is the gangue acid leaching residue; wherein the solid-liquid ratio of the activated gangue powder to the hydrochloric acid is 1:4; (4) adding sodium aluminate to the aluminum chloride solution obtained in step (3), adjusting the pH value of the reaction system to 3.5, and then stirring at 85° C. for 1.5 h to carry out polymerization reaction. After the polymerization reaction is completed, aging at 25° C. for 24 h to obtain a polyaluminum chloride coagulant; (5) washing the gangue acid leaching residue obtained in step (3) with deionized water for three times and then drying it, adding lanthanum nitrate and cerium sulfate solution, stirring at 25° C. for 1.5 h to fully impregnate it to obtain the gangue acid leaching residue loaded with cerium and lanthanum, wherein the molar ratio of lanthanum nitrate to cerium sulfate is 1:1, and the loading ratio of lanthanum to cerium is 20%; (6) After drying, the coal gangue acid leaching slag loaded with cerium and lanthanum obtained in step (5) is placed in a muffle furnace and calcined at 550° C. for 0.5 h to obtain a defluorination adsorbent.
[0035] Preparation Example 3 (1) Grinding the lump coal gangue with a ball mill and then sieving to obtain 150 mesh coal gangue powder; (2) placing the gangue powder obtained in step (1) in a muffle furnace and calcining it at 850° C. for 2.5 h, and then cooling the furnace naturally to obtain activated gangue powder; (3) dispersing the activated gangue powder obtained in step (2) in a 20% by mass hydrochloric acid solution, and centrifuging the solid-liquid mixture after acid leaching at 80° C. for 2.5 h, wherein the supernatant obtained is an aluminum chloride solution, and the remaining solid matter is the gangue acid leaching residue; wherein the solid-liquid ratio of the activated gangue powder to the hydrochloric acid is 1:3; (4) adding sodium aluminate to the aluminum chloride solution obtained in step (3), adjusting the pH value of the reaction system to 4, and then stirring at 90° C. for 1.5 h to carry out polymerization reaction. After the polymerization reaction is completed, aging at 30° C. for 24 h to obtain a polyaluminum chloride coagulant; (5) washing the gangue acid leaching residue obtained in step (3) with deionized water three times and then drying it, adding lanthanum nitrate and cerium sulfate solution, stirring at 25° C. for 1.5 h to fully impregnate it to obtain the gangue acid leaching residue loaded with cerium and lanthanum, wherein the molar ratio of lanthanum nitrate and cerium sulfate is 1:1, and the loading ratio of lanthanum and cerium is 25%; (6) After drying, the coal gangue acid leaching slag loaded with cerium and lanthanum obtained in step (5) is placed in a muffle furnace and calcined at 600° C. for 0.5 h to obtain a defluorination adsorbent.
[0036] Application Example 1 (1) Prepare 1000 mg / L sodium fluoride solution with sodium fluoride, then dilute it to 50 mg / L. Take 100 ml of 50 mg / L sodium fluoride solution into a polyethylene bottle, add a certain amount of kaolin, and stir thoroughly until the turbidity of the solution reaches 30 NTU; obtain simulated mine water containing fluoride ions with a concentration of 50-150 mg / L. (2) Weigh 0.3 g of the polyaluminium chloride coagulant and 0.1 g of the defluorination adsorbent prepared in Preparation Example 1 respectively; (3) The pH value of the sodium fluoride solution in step (1) was adjusted to 1, 3, 5, 7, 9, and 11, and then 0.3 g of polyaluminium chloride coagulant was placed in a polyethylene bottle to perform coagulation and precipitation at room temperature. The coagulation time was 30 min, and the turbidity removal rates were measured to be 23.6%, 35.4%, 51.8%, 75.7%, 89.5%, and 92.6%, respectively; (4) The solution after coagulation and precipitation in step (3) was filtered, and 0.1 g of defluorination adsorbent was added thereto. The solution was subjected to adsorption treatment at room temperature. After oscillation in a water bath constant temperature oscillator for 9 h, the solution was centrifuged and the fluoride ion concentration was measured. The adsorption amounts were 23.12 mg / g, 38.59 mg / g, 47.322 mg / g, 36.55 mg / g, 18.54 mg / g and 1.39 mg / g, respectively.
[0037] Application Example 2 (1) Prepare 1000 mg / L sodium fluoride solution with sodium fluoride, then dilute it to 50 mg / L. Take 100 ml of 50 mg / L sodium fluoride solution into a polyethylene bottle, add a certain amount of kaolin, and stir thoroughly until the turbidity of the solution reaches 30 NTU; obtain simulated mine water containing fluoride ions with a concentration of 50-150 mg / L. (2) Weigh 0.3 g of the polyaluminium chloride coagulant and 0.1 g of the defluorination adsorbent prepared in Preparation Example 1 respectively; (3) After adjusting the pH value of the sodium fluoride solution in step (1) to 5, 0.3 g of polyaluminium chloride coagulant was placed in the polyethylene bottle and coagulated and precipitated at room temperature. The coagulation times were 10, 20, 30, 40 and 50 min, respectively. The turbidity removal rates were 59.1%, 68.3%, 77.5%, 86.7% and 90.1%, respectively. (4) Add 0.1 g of defluorination adsorbent to the polyethylene bottle in step (3), conduct adsorption treatment at room temperature, oscillate in a water bath constant temperature oscillator for 1, 2, 4, 6, and 9 h, respectively, and then centrifuge to measure the fluoride ion concentration. The adsorption amounts are 44.75 mg / g, 44.39 mg / g, 45.06 mg / g, 46.59 mg / g, and 47.43 mg / g, respectively.
[0038] Application Example 3 (1) Prepare 1000 mg / L sodium fluoride solution with sodium fluoride, then dilute it to 50 mg / L. Take 100 ml of 50 mg / L sodium fluoride solution into a polyethylene bottle, add a certain amount of kaolin, and stir thoroughly until the turbidity of the solution reaches 30 NTU; obtain simulated mine water containing fluoride ions with a concentration of 50-150 mg / L. (2) Weigh 0.3 g of the polyaluminium chloride coagulant and 0.1 g of the defluorination adsorbent prepared in Preparation Example 1 respectively; (3) After adjusting the pH value of the sodium fluoride solution in step (1) to 5, 0.3 g of polyaluminium chloride coagulant was placed in the bottle and coagulation and precipitation were performed at 25°C, 35°C and 45°C, respectively. The coagulation time was 30 min, and the turbidity removal rates were measured to be 89.8%, 91.6% and 93.2%, respectively. (4) Add 0.1 g of defluorination adsorbent to the polyethylene bottle in step (3), perform adsorption treatment at 25°C, 35°C, and 45°C, oscillate in a water bath constant temperature oscillator for 9 hours, and then centrifuge to measure the fluoride ion concentration. The adsorption amounts are 45.16 mg / L, 42.42 mg / L, and 41.12 mg / L, respectively. Figure 3 As shown, with the increase of pH value, the adsorption amount of fluoride ions shows a trend of first increasing and then decreasing. When the pH value is 5, the adsorption performance of the defluorination adsorbent is the best.
[0039] The above embodiment provides a detailed description of the present invention, but it is only a part of the embodiments of the present invention, rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a fluorine-containing mine water treatment agent using coal gangue as all components, characterized in that: The steps include: Step (1): grinding the coal gangue block by a ball mill and then sieving it into coal gangue powder; Step (2): placing the gangue powder obtained in step (1) in a muffle furnace for high-temperature calcination and activation, and then naturally cooling the furnace to obtain activated gangue; Step (3): dispersing the activated coal gangue obtained in step (2) in a hydrochloric acid solution, centrifuging the solid-liquid mixture after the acid leaching reaction, and obtaining a supernatant as an aluminum chloride solution and a precipitate as coal gangue acid leaching residue; Step (4): adding sodium aluminate to the aluminum chloride solution obtained in step (3), adjusting the pH value of the reaction system to 3 to 5, performing a polymerization reaction and aging to obtain a polyaluminum chloride coagulant; Step (5): washing the coal gangue acid leaching residue obtained in step (3) with deionized water three times and then drying, adding lanthanum nitrate and cerium sulfate solution, stirring at 25 to 45° C. for 1 to 1.5 hours to fully impregnate the coal gangue acid leaching residue to obtain cerium and lanthanum loaded; Step (6): after drying, the cerium and lanthanum loaded on the coal gangue acid leaching slag obtained in step (5) is placed in a muffle furnace for high-temperature roasting to obtain a defluorination adsorbent; Step (7): The polyaluminium chloride coagulant and the defluorination adsorbent together constitute a fluorine-containing mine water treatment agent, wherein the polyaluminium chloride coagulant is used to remove suspended matter in the fluorine-containing mine water, and the defluorination adsorbent is used to remove fluoride ions in the fluorine-containing mine water.
2. The method for preparing a fluorine-containing mine water treatment agent using coal gangue as all components according to claim 1, characterized in that: The particle size of the coal gangue powder after ball milling in step (1) is 150 mesh.
3. The method for preparing a fluorine-containing mine water treatment agent using coal gangue as all components according to claim 1, characterized in that: The high temperature calcination activation in step (2) has a calcination temperature of 700 to 850° C. and a calcination time of 1.5 to 2.5 hours.
4. The method for preparing a fluorine-containing mine water treatment agent using coal gangue as all components according to claim 1, characterized in that: The solid-liquid ratio of the activated coal gangue to the hydrochloric acid solution in step (3) is 1:3 to 1:5; the mass fraction of the hydrochloric acid solution is 20%, the acid leaching temperature is 80 to 95° C., and the acid leaching time is 1.5 to 2.5 hours.
5. The method for preparing a fluorine-containing mine water treatment agent using coal gangue as all components according to claim 1, characterized in that: In step (4), the polymerization temperature is 70-90°C, the polymerization time is 1-2h, the aging temperature is 20-30°C, and the aging time is 20-30h.
6. The method for preparing a fluorine-containing mine water treatment agent using coal gangue as all components according to claim 1, characterized in that: In step (5), the solid-liquid ratio of the coal gangue acid leaching residue to the lanthanum nitrate and cerium sulfate solution is 1:1 to 1:3; the molar ratio of lanthanum nitrate to cerium sulfate is 1:1; and the loading ratio of lanthanum to cerium is 15 to 35%.
7. The method for preparing a fluorine-containing mine water treatment agent using coal gangue as all components according to claim 1, characterized in that: The calcination temperature in step (6) is 500-650° C., and the calcination time is 0.3-1 h.
8. Use of a fluorine-containing mine water treatment agent composed of a polyaluminium chloride coagulant and a defluorination adsorbent prepared according to the method of any one of claims 1 to 7 in the treatment of fluorine-containing mine water.
Citation Information
Patent Citations
Method for producing poly silicate aluminium ferric flocculating agent by utilizing coal gangue
CN101823721A
A method for producing polyaluminum chloride
CN102295305A
Clean poly-generation preparation method for flyash with high-content silicon dioxide
CN104445311A
Efficient fluorine removal agent and preparation method thereof
CN116102142A
Two methods for extracting gallium from fly ash
DE112011101461T5